Precautions Taken Against the COVID-19 by Presidency of Religious Affairs in terms of Hajj and Umrah pilgrimage: The case of Turkey - Akbulut, Onur (The international journal of religious tourism and pilgrimage, 2020)
The gathering of people in a concentrated manner within particular spaces / places has become a serious issue during the COVID-19 pandemic period. Mass gatherings of individuals seem to be investigated intensively by researchers both in these days and will be further in the forthcoming years. Religion-oriented gatherings are of great importance because they have spiritual motivation for the ones who practice them. For many participants, these gatherings are essential at least once in their life. As is seen from its very nature, religious motivation is one of the most potent subjects to be considered in terms of mass gatherings. Thus, as a useful example, the pilgrimage in Islam to Hajj and Umrah in Saudi Arabia are the focus of this study. The international movements and gatherings stemming from religious motivation are a point of discussion in terms of the precautions which should be taken. Therefore, in this study, general information about these particular pilgrimages is provided, and the specific case of Turkey in relation to the COVID-19 pandemic is investigated within the scope of the precautions taken by the Turkish authorities. The study was designed to present the publicly announced precautions organised by the official response to Turkish pilgrims by the Presidency of Religious Affairs.